(untitled) (Argos, 2025)
Our paper aims to check an intertextual boundary suggested but not proved by critics: the one that might exist between Faunus’ prophecy in Calp. 1. 33-88 and Nero’s address to the Senate as he carne to the power in 54 a.D. Based on the «reconstruction» of the Emperor’s lost speech according to the summary provided by Tacitus, Ann. 13. 4. 1-3, detailed comparative examination of both texts reveals the emergency in Calpurnius of the three main arguments that may have organized the inventio of the Emperor’s speech.